2015
DOI: 10.1159/000434728
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CPP-ACP Paste on Enamel Carious Lesion of Primary Upper Anterior Teeth Assessed by Quantitative Light-Induced Fluorescence: A One-Year Clinical Trial

Abstract: The purpose of this clinical trial was to evaluate the effect of 1 year of daily application of 10% w/v CPP-ACP (casein phosphopeptide-amorphous calcium phosphate) paste in addition to regular toothbrushing with fluoridated toothpaste on the remineralization of enamel carious lesions in preschool children using quantitative light-induced fluorescence (QLF). A total of 103 Thai children (aged 21/2-31/2 years) with high caries risk who had at least 1 enamel carious les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 18 publications
(16 reference statements)
1
30
0
Order By: Relevance
“…Both in-vitro and in-situ studies have demonstrated that CPP-ACP can promote the remineralization of subsurface enamel lesions 10,12) Thirty six weeks after debonding in our study, the lesions showed significant improvement with respect to fluorescence loss, as monitored by DD. However, both test and control methods resulted in significant improvements of WSLs severity and activity scores compared to baseline, but no significant differences were detected between the groups after three years.…”
Section: Discussionsupporting
confidence: 51%
See 4 more Smart Citations
“…Both in-vitro and in-situ studies have demonstrated that CPP-ACP can promote the remineralization of subsurface enamel lesions 10,12) Thirty six weeks after debonding in our study, the lesions showed significant improvement with respect to fluorescence loss, as monitored by DD. However, both test and control methods resulted in significant improvements of WSLs severity and activity scores compared to baseline, but no significant differences were detected between the groups after three years.…”
Section: Discussionsupporting
confidence: 51%
“…Our bacterial results should be interpreted with caution because of dropout rate. The study period of 36 weeks might be regarded as long compared with other studies [11][12][13][14][15][16] , so the dropout rate in this study is relatively high (17%). So we failed to detect any positive or negative effects of CPP-ACP on saliva bacterial levels 30) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations